Promoting Local Acceptability of International Oil Companies (IOCS) Through Corporate Social Responsibility (CSR): The Case of Tullow Oil in Ghana - Fragouli, Evangelia; Danyi, Aiden Yengbalang (Financial Risk and Management Reviews, 2015)
Ghana discovered oil in commercial quantities in 2007 following intense exploration works by Tullow Oil Plc and Kosmos Energy. Ghanaians are expecting more benefits from government and the International Oil Companies (IOCs) in particular. This study is aimed at assessing the global integration and local responsiveness strategies of IOCs in Ghana and how that impacts on the acceptability of the operations of these IOCs by locals presenting Tullow as a case study. Main research questions refer to how these local expectations can be properly managed, how IOCs can design and properly implement their CSR obligations and the extent to which the pursuit of CSR activities by IOCs can help promote their local acceptability in Ghana. An empirical study with a qualitative analysis approach was applied to obtain primary information from Tullow Oil Plc, government agencies, Civil Society Organisations (CSOs), and local communities. The study established a positive relationship between good CSR practice and local acceptability. Even though some of the local people acknowledged the benefits of Tullow’s CSR activities, others do not, but express a continuous desire for IOCs and Tullow in particular to do more.